Effect of Polymeric Nanoparticles with Entrapped Fish Oil or Mupirocin on Skin Wound Healing Using a Porcine Model - Komprda, Tomáš; Sládek, Zbyšek; Vícenová, Monika; Simonová, Jana; Franke, Gabriela; Lipový, Břetislav; Matejovičová, Milena; Kacvinská, Katarína; Sabliov, Cristina; Astete, Carlos E; Levá, Lenka; Popelková, Vendula; et al. (International journal of molecular sciences, 2022)
The utilization of poly(lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) with entrapped fish oil (FO) loaded in collagen-based scaffolds for cutaneous wound healing using a porcine model is unique for the present study. Full-depth cutaneous excisions (5 × 5 cm) on the pig dorsa were treated with pure collagen scaffold (control, C), empty PLGA NPs (NP), FO, mupirocin (MUP), PLGA NPs with entrapped FO (NP/FO) and PLGA NPs with entrapped MUP (NP/MUP). The following markers were evaluated on days 0, 3, 7, 14 and 21 post-excision: collagen, hydroxyproline (HP), angiogenesis and expressions of the COX2, EGF, COL1A1, COL1A3, TGFB1, VEGFA, CCL5 and CCR5 genes. The hypothesis that NP/FO treatment is superior to FO alone and that it is comparable to NP/MUP was tested. NP/FO treatment increased HP in comparison with both FO alone and NP/MUP (day 14) but decreased (p < 0.05) angiogenesis in comparison with FO alone (day 3). NP/FO increased (p < 0.05) the expression of the CCR5 gene (day 3) and tended (p > 0.05) to increase the expressions of the EGF (day 7, day 14), TGFB1 (day 21) and CCL5 (day 7, day 21) genes as compared with NP/MUP. NP/FO can be suggested as a suitable alternative to NP/MUP in cutaneous wound treatment.
Keywords: nanoparticles; hydroxyproline; prasata; Swine; cutaneous wounds; Mupirocin; Polylactic Acid-Polyglycolic Acid Copolymer; Nanoparticles; nanočástice; kolagen; Epidermal Growth Factor; transforming growth factor; collagen; rybí oleje; Animals; Fish Oils; Wound Healing; cyclooxygenase-2; zvířata; kopolymer kyseliny glykolové a mléčné; Collagen; poly(lactic-co-glycolic) acid; epidermální růstový faktor; mupirocin; polyunsaturated fatty acids n-3; hojení ran